Acessibilidade em edifícios públicos de cultura em uma cidade de médio porte do estado de São Paulo - Gomes, Luciene (2014)
Since diversity is a characteristic of human beings, a crucial feature of any environment, space or object intended for use by anyone is accessibility. The city has to accommodate these differences and be adapted architectonically to enable the integration of all its dwellers. The idea driving this project is the belief that architectural planning is a potential ally in furthering the social inclusion of people with a disability or reduced mobility. This study thus deals with issues related to their access to cultural facilities, particularly by raising questions concerning the specific legislation and technical standards created to help people with disabilities. Specifically, the aim was to analyze accessibility in seven municipal cultural institutions in São Carlos city in upstate São Paulo, two of which are in outlying municipal districts. Public cultural buildings were chosen for study in the belief that a person with disability should have the same opportunities to participate in cultural life as any other person, thus becoming integrated into society. Cultural spaces should be duly adapted and accessible to the various forms of perception, locomotion and communication characteristic of an inclusive society. All cultural buildings in the chosen area were visited and, using a checklist stipulated by the Brazilian Association of Technical Standards (NBR 9050, 2004), the public spaces were classed as adequate or inadequate with respect to their accessibility to people with a disability (either visual or physical).The data collected was subjected to quantitative analysis by scoring the commonest accessibility resources, according to their adequacy, as well as the resources not installed. The results show that in all the items analysed, both in the internal and external spaces of the buildings under study, there is a need for adaptations, installations or the building of equipment that allows the physically or visually disabled to interact with the environment in the cultural spaces they choose. By indicating the state of the art in the chosen city, this study contributed to the body of knowledge in the area of accessibility.